"Meth's Not My Cup of Tea": Perceptions of Methamphetamine Among Black Women. (October 2014) - Copes, Heith; Kerley, Kent R.; Angulski, Kate; Zaleski, Samantha
Recent media portrayals of methamphetamine (meth) suggest that its use is relatively rare among Black drug users. Our aim with the current research is to explore the reasons why Black women stimulant users abstain from using meth. We rely on semi-structured interviews with 33 Black women whose drug of choice was cocaine and who had never or rarely used meth. These women said that they did not use meth because they had limited access to the drug, feared the chemicals used in production, disliked the immediate sensations, and feared the long-term consequences on their health. The limited access to meth led these stimulant users to rely on stereotypes of meth that the drug is made from toxic materials and that it causes rapid deterioration in users' appearances. We argue that these factors contribute to meth use being stigmatized in Black communities, thereby acting as a protective factor in discouraging use among Black stimulant users.